Effects of combined endurance and resistance training in Amyotrophic Lateral Sclerosis: A pilot, randomized, controlled study - Antonio Merico; Marianna Cavinato; Caterina Gregorio; Alessandra Lacatena; Elisabetta Gioia; Francesco Piccione; Corrado Angelini (European Journal of Translational Myology, 2018)
Based on available evidence, muscle strengthening and cardiovascular exercises can help maintain function and not adversely affect the progression of disease in patients with ALS. However, this evidence is not sufficiently detailed to recommend a specific exercise prescription. The purpose of this project was to assess clinical outcomes of a combined exercise programme to increase knowledge of rehabilitation in ALS patients. 38 ALS patients were assigned randomly to two groups: one group underwent a specific exercise programme (ALS-EP) based on a moderate aerobic workout and isometric contractions, and the second group followed a standard neuromotor rehabilitation treatment. Objective evaluation consisted of cardiovascular measures, muscle strength and fatigue. Some positive effects of physical activity on ALS patients were found. Among the benefits, an overall improvement of functional independence in all patients, independently of the type of exercise conducted was seen. In addition, improvements in muscle power, oxygen consumption and fatigue were specifically observed in the ALS-EP group, all hallmarks of a training effect for the specific exercises. In conclusion, moderate intensity exercise is beneficial in ALS, helping in avoiding deconditioning and muscle atrophy resulting from progressive inactivity.